DEVELOPMENT OF COMPARATIVE EDUCATION WORLDWIDE AND AT UNIVERSITIES OF LITHUANIA - Želvys, Rimantas; Wolhuter, Charl C. (Acta Paedagogica Vilnensia, 2014)
This article compares the state of the field of Comparative Education in Lithuania with developments internationally. As in most of the countries of the erstwhile Eastern Bloc, the confluence of circumstances in the past decades resulted in Comparative Education being strongly and visibly present in courses taught at pre-graduate and postgraduate levels at universities in Lithuania since 1990. What is absent are research institutes of Comparative Education, also established chairs of Comparative Education, Comparative Education departments and academics exclusively occupied with (teaching and conducting research in) Comparative Education. Comparativists in Lithuania are also not strongly connected with each other and with the international Comparative Education community. While Comparative Education research gets done vigorously and the themes of research are very topical and include equity issues (including gender equity), quality and quality assurance, internationalization of higher education, the societal effects of education (e.g., the effect of education on values, including the political values of students, the effect of education on economic development or on social mobility) and research on the learning of students.
Keywords: Comparative Education; Lithuania; education research agenda; teacher education